Sosialisasi Keterampilan Pengolahan Limbah Padat Ikan Menjadi Makanan Kemasan Bernilai Ekonomis di Kelompok Pengolah dan Pemasar Ikan Al-Ijtihad Kelurahan Penkase Oeleta Kota Kupang - Syarifuddin Darajad; Yahya Nobisa; Wahid Hasyim Tra Beni; Arifin; Zainur Wula; Hadjrah Arifin; Amirullah Datuk; Evelyn Belaktrix Sumby; Sulaiman Mustafa Wuhdin; Kamis Karno; Fazlul Rahman RM; Masita Bareut (University of Muhammadiyah Malang, 2025)
This community service activity aims to address the curiosity of young people about processing solid fish waste into economical packaged food. Supported by Muhammadiyah University, this initiative integrates entrepreneurial and sociological studies into academic curricula for coastal communities, enhancing the practical application of theoretical knowledge. The activity involved 15 young participants, with 10 completing the program successfully. The method used was a combination of lectures and hands-on practice in processing solid fish waste into products like fish bone chips and sticks. The detailed processing steps served as a guide for participants to develop their skills. Results show high enthusiasm among participants, with 20 out of 25 completing the training effectively. The program successfully enhanced knowledge and skills in utilizing fish waste to create economical products, meeting the planned targets. This initiative improves young people's skills in processing fish waste, benefiting income and the environment. Its novelty lies in a practical, interdisciplinary approach, providing an innovative solution for optimizing fish waste.